2014
DOI: 10.12720/sgce.3.2.247-254
|View full text |Cite
|
Sign up to set email alerts
|

Grid-connected photovoltaic module and array sizing based on an iterative approach

Abstract: This paper deals with the sizing of a simple but efficient grid-connected photovoltaic (GCPV) system to minimize the difference between the electrical energy generated by the GCPV system and the required energy. It provides a technical sizing procedure based on an iterative approach for meeting specific amount of GWh output required by a future PV system considered for Kuwait. The iterative sizing algorithm has been implemented to determine the configuration of the PV array, actual rated output power with its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Several models have been developed to model these systems. Alenezi et al [7] developed an iterative approach to sizing a grid-connected PV system and found that technical outputs such as the number of PV modules, PV panel configuration, and inverter sizing are most important of the algorithm for integration to the grid. Huang et al [8] found that the performance of a PV system is mainly influenced by weather, solar irradiance, and module temperature and were able to develop an evolutionary programming algorithm to predict the performance of a grid-connected PV system based on those influences.…”
Section: Introductionmentioning
confidence: 99%
“…Several models have been developed to model these systems. Alenezi et al [7] developed an iterative approach to sizing a grid-connected PV system and found that technical outputs such as the number of PV modules, PV panel configuration, and inverter sizing are most important of the algorithm for integration to the grid. Huang et al [8] found that the performance of a PV system is mainly influenced by weather, solar irradiance, and module temperature and were able to develop an evolutionary programming algorithm to predict the performance of a grid-connected PV system based on those influences.…”
Section: Introductionmentioning
confidence: 99%